The Effect of New Yogyakarta International Airport (NYIA) Development Against Development Infrastructure in Kulonprogo - Indreswari Suroso (Departement of Architecture, Universitas Islam Indonesia, 2018)
The development of national transportation network includes land, sea and air transportation. This research aims to analyze the influence of new airport development in Kulonprogo named New Yogyakarta International Airport (NYIA) towards infrastructure development in Kulonprogo. The influence of NYIA on Kulonprogo infrastructure is massive, namely, the extension of national road to Kulonprogo Regency located in Milir Hamlet, Kedungsari Village, Pengasih Subdistrict, and bridge construction in Sentolo Subdistrict that connects between Bantul, Sleman and Kulonprogo districts. In addition to the construction of roads and bridges, the construction of infrastructure connects to Borobudur temple in Magelang regency under the term of Menoreh Surgery involving the land acquisition of Kulonprogo residents, investors and housing developers invest land in Kulonprogo to build hotel and housing near the new airport plan. The obstacles in the relocation of affected residents of this airport are the construction of public facilities and social facilities such as the availability of clean water, electricity network and household sanitation at the beginning of development that is important to support the basic needs. Public facilities and social facilities development are conducted by the Ministry of Public Works and Public Housing. The affected residents at Glagah Village, Palihan Temon Kulonprogo District refused to be relocated in case social facilities and public facilities are not available. The local government approach personally to the affected villagers by accelerating the relocation process and working with various stakeholders.Keywords: transportation, airport, local government, kulonprogo.